Brexit Disorientation and Cultural Fragmentation in Ali Smith's Autumn: A Constructivist Analysis - Ahmed Abdel-Fattah Eid; Marwan Kadhim Mohammed (Universiti Sains Islam Malaysia, 2026)
International Conference of Language & Education (iLEC2025): Empowering Language and Education to Develop Madani Generation in the Era of Artificial Intelligence (AI) 17 & 18 November 2025 Organized by Universiti Sains Islam Malaysia